THE INFLUENCE OF HALAL LOGO ON THE PURCHASING BEHAVIOR OF MUSLIM FILIPINOS: A STRUCTURAL EQUATION MODELLING - Aldrich June B. Caraecle; Mohammad Rehan D. Raopan (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
The study investigated the influence of halal logo on the purchasing behavior of Muslim Filipinos. Moreover, it assessed the knowledge, attitude and the perceived issues of consumers toward halal logo, thereby gain a deeper understanding of the critical factors that shape consumer behavior. A quantitative research design was employed, utilizing a structured questionnaire administered to a sample of 400 Muslim Filipino consumers. Cronbach’s alpha was tested to assess the reliability of the instrument. The instrument was also validated by research experts to ensure its functionality. Furthermore, the validity of the instrument was measured by convergent validity test. Descriptive statistics and PLS-Structural Equation modelling were used to analyze the data gathered. The findings of the study revealed the important role of Halal logo in influencing consumers’ purchasing behavior. The respondents expressed a strong commitment to checking for the Halal logo, double-checking its presence, and exclusively buying products with the Halal logo. They are willing to pay a premium for products with the Halal certification, highlighting the importance of the logo as a guiding factor in their decision-making process. Based on the PLS-SEM, the attitude and the issues perceived by the Muslim consumers on products with halal logo have an influence on their purchasing behavior. With these findings, it is recommended that consumer protection measures be intensified to safeguard the rights and interests of Muslim Filipino consumers. Regulatory agencies, manufacturers, and retailers should ensure accurate and reliable halal certification processes and enforce strict adherence to Halal standards. Importantly, efforts should be made to raise awareness among Muslim consumers about the significance of the halal logo and the assurance it provides in terms of product quality and compliance with religious requirements.